PELAKSANAAN GOOD TOURISM GOVERNANCE OLEH PEMERINTAH DESA DAN STAKEHOLDERS DI DESA ALIANTAN KECAMATAN KABUN KABUPATEN ROKAN HULU TAHUN 2022 - Manalu, Nengsih; Handoko, Tito (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research delves into the implementation of the Good Tourism Governance (GTG) concept by the village government and stakeholders in Aliantan Village, particularly in the context of tourism management. The main objective of the research is to analyze the management carried out by the village government and stakeholders in applying the principles of GTG for tourism development. The research method employed is a qualitative approach through in-depth interviews with the village government, local stakeholders, and tourism observers. This approach is designed to gain a profound understanding of the implementation practices of GTG and the roles of stakeholders in tourism management in Aliantan Village. The research results indicate that the village government has implemented several measures in applying the concept of Good Tourism Governance (GTG) for tourism development in Aliantan Village. The steps taken include active involvement of various stakeholders in the decision-making process, transparency in resource management, and community participation in the planning and implementation of tourism activities. However, the study identified some challenges, including a lack of effective coordination between the village government and stakeholders, potentially hindering the implementation of Good Tourism Governance. Awareness of the importance of GTG in sustainable tourism development is also identified as an area that needs improvement. The research concludes that although efforts have been made to implement the principles of Good Tourism Governance, there is a need for further steps to strengthen collaboration between the village government and stakeholders. Additionally, an enhanced understanding of GTG at the local level is considered essential to improve the effectiveness of tourism management in Aliantan Village. These findings provide actionable insights for improving the quality of GTG implementation at the village level and offer direction for future improvement efforts. Keywords: Aliantan Village, Good Tourism Governance, Tourism Development, Tourism Sustainability, Village Government